Identification of the cerebral effects of paracetamol in healthy subjects: an fMRI study. Issue 1 (February 2020) - De Coster, Olivier; Forget, Patrice; De Mey, Johan; Van Schuerbeek, Peter; Poelaert, Jan
Introduction: Paracetamol is commonly used for its antipyretic properties and analgesic effects, but the central mechanism remains elusive. We designed a study in healthy volunteers to detect the central functional working mechanism of paracetamol. Subjects, material and methods: A total of 20 subjects had a baseline functional magnetic resonance imaging (fMRI) before the intake of 1000 mg paracetamol orally; 60 minutes later, a second fMRI was made aiming detection of regional blood flow differences. Results: A decreased connectivity was observed in the ventral volume of interest (VOI), with the posterior cingulate (with both the left anterior cingulate cortex (ACC) and right ACC: respectively, Ke = 576; t = −6.8894 and Ke = 185; t = −4.8178) and the inferior temporal left (Ke = 103; t = −5.0993); in the combined ventral and dorsal VOIs, the posterior cingulate (with the left ACC; Ke = 149; t = −4.5658) and, both with the right ACC, the inferior temporal left (Ke = 88; t = −3.8456) and the inferior frontal gyrus (Ke = 86; t = −4.3937) had a decrease in connectivity. An increase was seen in other regions, including, among others, the middle frontal and temporal gyri (respectively, Ke = 85; t = 4.4256 and Ke = 85; t = 5.6851), the inferior frontal (with the left ACC: Ke = 165; t = 4.4998) and the superior frontal gyrus (with the right ACC; Ke = 281; t = 4.5992), and the post/precentral gyrus (with the right ACC, respectively, Ke = 102; t = 6.0582 and Ke = 105; t = 4.0776). Conclusions: On fMRIs in healthy volunteers, the ingestion of paracetamol affects connections with the ACC. This suggests a central effect of paracetamol in cerebral areas known to be associated with pain. Further studies are needed to demonstrate the same effects in acute and chronic pain states.